Conditional sanctioning in a legume-Rhizobium mutualism - Westhoek, A; Clark, LJ; Culbert, M; Dalchau, N; Griffiths, M; Jorrin, B; Karunakaran, R; Ledermann, R; Tkacz, A; Webb, I; James, E; Poole, PS; et al. (National Academy of Sciences, 2021)
Legumes are high in protein and form a valuable part of human diets due to their interaction with symbiotic nitrogen-fixing bacteria known as rhizobia. Plants house rhizobia in specialized root nodules and provide the rhizobia with carbon in return for nitrogen. However, plants usually house multiple rhizobial strains that vary in their fixation ability, so the plant faces an investment dilemma. Plants are known to sanction strains that do not fix nitrogen, but nonfixers are rare in field settings, while intermediate fixers are common. Here, we modeled how plants should respond to an intermediate fixer that was otherwise isogenic and tested model predictions using pea plants. Intermediate fixers were only tolerated when a better strain was not available. In agreement with model predictions, nodules containing the intermediate-fixing strain were large and healthy when the only alternative was a nonfixer, but nodules of the intermediate-fixing strain were small and white when the plant was coinoculated with a more effective strain. The reduction in nodule size was preceded by a lower carbon supply to the nodule even before differences in nodule size could be observed. Sanctioned nodules had reduced rates of nitrogen fixation, and in later developmental stages, sanctioned nodules contained fewer viable bacteria than nonsanctioned nodules. This indicates that legumes can make conditional decisions, most likely by comparing a local nodule-dependent cue of nitrogen output with a global cue, giving them remarkable control over their symbiotic partners.